1995
DOI: 10.2307/2269340
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Developing Sustainable Extraction Systems for Tropical Forest Products

Abstract: There are few if any examples of the demonstrably sustainable extraction of either timber or non—timber forest products. Even well—known products such as brazil nuts and mahogany lack a sufficient knowledge base to design a sustainable extraction system. Potential extraction systems for timber and non—timber forest products from tropical forests should be evaluated both in terms of their sustainability and their impact at the ecosystem level. The impact of forest product harvest on the demographics of the targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 25 publications
0
69
0
4
Order By: Relevance
“…Factors like total forested area, access, historic use of both target and non-target species and observation of land use patterns in adjacent areas have a dramatic impact on the forest development, which contributes to supply and the sustainable use (Howard 1993). If the harvesting quotas, established based on the original total area, continue despite reductions in supply area, harvesting per unit area will exceed growth and yield, leading to depletion of the target species (Boot & Gullison 1995). Earlier Markegaon forest was well managed hence maximum girth rate of the vegetation with more number of older trees was found, however, in recent times it was disturbed.…”
Section: Institutional Analysismentioning
confidence: 99%
“…Factors like total forested area, access, historic use of both target and non-target species and observation of land use patterns in adjacent areas have a dramatic impact on the forest development, which contributes to supply and the sustainable use (Howard 1993). If the harvesting quotas, established based on the original total area, continue despite reductions in supply area, harvesting per unit area will exceed growth and yield, leading to depletion of the target species (Boot & Gullison 1995). Earlier Markegaon forest was well managed hence maximum girth rate of the vegetation with more number of older trees was found, however, in recent times it was disturbed.…”
Section: Institutional Analysismentioning
confidence: 99%
“…Studies have shown that in combination net present values can double or even triple with NTFPs often providing the majority of income (Peters et al 1989a, b;Godoy et al 1993;Boot and Gullison 1995;Ashton et al 2001b). Regional examples are provided in the following sections.…”
Section: Uses Of Important Tropical Timber and Ntfpsmentioning
confidence: 99%
“…Longterm vegetation monitoring through permanent plots is widely used to provide an insight into regeneration behaviour and vegetation dynamics as well as growth and mortality patterns (Bakker et al 1996). Data from permanent plots allow study of the effects of many factors on tree growth through mathematical models, providing useful tools for forest management (Alder 1995;Boot and Gullison 1995;Alder 2002). In this study, we use data from permanent sample plots in a mono-specific black beech forest (Fuscospora solandri (Hook.f.)…”
Section: Introductionmentioning
confidence: 99%